Urban Environment Management as Instrument to Increase Local Ability and Human Resources - Eddy, Triono (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Urban Environment Management as Instrument to Increase Local Ability and Human Resources